Afetos e novidades aparecidas em um percurso de teatro do oprimido na saúde mental - Lins , Claudete do Amaral (2018)
The present dissertation aims to map a Theater of the Oppressed course in mental health. In the context of psychiatric reform, the search for other forms of expression and production of subjectivity is current and pressing, due to the social inequalities experienced, as well as the lack of public policies and setbacks in mental health policy. The question of the research is "how the Theater of the Oppressed operates in the singularization of people in psychic suffering?" Through the affections and novelties that appear in this course, the objective is to analyze more specifically how the Theater of the Oppressed operated in the production of subjectivity and singularization of people with psychic suffering during the Theater of the Oppressed workshops. New appearances are allusive to the name given to the piece of Theater Forum produced during the process, this one was constructed from the real history of one of the participants of the Theater of the Oppressed. The methodology that underlies this work is the qualitative descriptive using the method of the intervention research, and more specifically the cartography. Teatro do Oprimido workshops were held for 7 months, Psychosocial Care Center - CAPS Casa Verde in Maceió with the participation of 30 people in the service. Participants and fellows were collective researchers and protagonists of the action. The research was linked to the Project of Extension - Theater of the Oppressed in mental health in Maceió through ProCCaext / 2016. From the process and experience of games and exercises of the Arsenal of the Theater of the Oppressed, the aesthetics of the oppressed and the construction and presentation of the play Theater Forum we produced this narrativity about the effects - subjectivity experienced in the workshops in the light of the practical philosophy of Espinosa, more specifically focusing on his theory of affects. In the production of the data we operate articulations of the Theater of the Oppressed with the espinosanos concepts to bring more elements that can answer the question of how the Theater of the Oppressed operates in the singularization of the people with psychic suffering. As results we can highlight the potentiation that occurred in the way of acting and reacting in the participants' daily lives, that is, in the affections - passions and affections - lived actions, in the understanding and in the dialogue with the production of more life. We conclude that the Theater of the Oppressed provides an intense experience of affections, feelings and acts and contributes to increase the power to act and produce more life, facing the suffering imposed by inequalities and illness. The power to act also acted to reduce the passivity against the suffered, the prejudice among other ideas imposed by society.